Jean-Christophe, Volume I - Rolland, Romain, 1866-1944; Cannan, Gilbert, 1884-1955 (Salt Lake City, UT : Project Gutenberg, 2005)
"Jean-Christophe, Volume I" by Romain Rolland is a novel published between 1904-1912. This ten-volume work tells the story of Jean-Christophe Krafft, a German musical genius living in France. From cradle to grave, he endures hardships and spiritual struggles, balancing pride in his talents with the need to survive. Tormented by injustice and forced to flee his brushes with authority, he searches for peace while navigating the complexities of art, society, and life across Europe. (This is an automatically generated summary.)
Dawn -- Morning -- Youth -- Revolt.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Jean-Christophe
Release date is 2005-04-01
E-text prepared by the Distributed Proofreading Team
Keywords: Psychological fiction; Epic literature; Musicians -- Fiction; French fiction -- Translations into Finnish